Are YouTube Videos Enough to Learn Anakinra Self-Injection - Pamukcu, Melih; Duran, Tugba Izci (Springer Heidelberg, 2021)
Anakinra is a drug that can be administered subcutaneously as a self-injection in both children and adults. We aimed to evaluate the content, reliability, and quality of the videos most viewed on "anakinra self-injection" on YouTube, which is an easily accessible source of information. We performed a YouTube search using the keywords "anakinra", "anakinra injection", and "anakinra self-injection" in addition to the generic and commercial names of the biologic agent in September 2021. The quality and reliability of the videos were assessed according to the Global Quality Score (GQS) and DISCERN score. Video power index was used to assess both the view and the like ratio of the videos. A total of 51 videos were analyzed, a majority of which were uploaded by physicians (56.9%). The median GQS was 3 and total DISCERN score was 49. According to the GQS, 21.6% of the videos were of low quality, 35.3% were of fair quality, and 43.1% were of high quality. High-quality videos had higher DISCERN scores and longer duration of videos (p < 0.05). 41 (80.4%) videos were categorized as useful information, and 8 (15.7%) as useful as per patients' opinion. Further, GQS and DISCERN scores of videos that had useful information were significantly higher. There are numerous YouTube videos with helpful information that can be a source of knowledge on the safe and correct technique of daily anakinra self-injection for both adults and children. There was no significant difference in patient interaction between useful and misleading videos. This indicates that patients do not differentiate between high- and low-quality videos.
Pamukcu, Melih/0000-0002-9129-0503;
Keywords: Anakinra Injection; Internet; Patient Education; Quality; Reliability; YouTube